Liberomycespistaciae sp. nov., the causal agent of pistachio cankers and decline in Italy - Vitale, Salvatore (MycoKeys, 2018)
Abstract. A new canker and decline disease of pistachio (Pistaciavera) is described from Sicily (Italy). Observations of the disease and sampling of the causal agent started in spring 2010, in the area where this crop is typically cultivated, Bronte and Adrano (Catania province) and later extended to the Agrigento and Caltanissetta provinces. Isolations from the margins of twig, branch and stem cankers of declining plants resulted in fungal colonies with the same morphology. Pathogenicity tests on 5-year-old potted plants of Pistaciavera grafted on P.terebinthus reproduced similar symptoms to those observed in nature and the pathogen was confirmed to be a coloniser of woody plant tissue. Comparison of our isolates with the type of the apparently similar Asteromellapistaciarum showed that our isolates are morphologically and ecologically different from A.pistaciarum, the latter being a typical member of Mycosphaerellaceae. Asteromellapistaciarum is lectotypified, described and illustrated and it is considered to represent a spermatial morph of Septoriapistaciarum. Multi-locus phylogenies based on two (ITS and LSU rDNA) and three (ITS, rpb2 and tub2) genomic loci revealed isolates of the canker pathogen to represent a new species of Liberomyces within the Delonicicolaceae (Xylariales), which is here described as Liberomycespistaciaesp. nov. (Delonicicolaceae, Xylariales). The presence of this fungus in asymptomatic plants with apparently healthy woody tissues indicates that it also has a latent growth phase. This study improves the understanding of pistachio decline, but further studies are needed for planning effective disease management strategies and ensuring that the pathogen is not introduced into new areas with apparently healthy, but infected plants.